EFFECTS OF TIO2 NANO-PRIMING ON TOMATO SEED GERMINATION AND PLANT DEVELOPMENT - Ayten Kubra Yagiz; Mehmet Emin Çaliskan (Journal of Animal and Plant Sciences, 2024)
The effect of nano-TiO2 on seed germination and plant development as a priming agent has not been thoroughly studied. This study aimed to evaluate the effect of TiO2 nano-priming on seed germination, plant growth and yield of tomato plants relying on experiments that have been conducted both under laboratory and greenhouse conditions. During the laboratory experiments, the seed germination, seed vigor index and water uptake of seeds were determined after 5, 10, 50 and 100 mg L-1 of TiO2 nano-priming while hydropriming was used as control. The biomass of tomato seedling was increased the most for the 10 mg L-1 TiO2 nano-priming condition. With follow-up experiments, the effect of 10 mg L-1 TiO2 nano-priming was investigated further under greenhouse conditions, where hydropriming was also used as control. The physiological traits of tomato plants, like chlorophyll content, stomatal conductance and transpiration rate were increased by TiO2 nano-priming treatment. Although the photosynthesis rate was boosted by nano-priming, the yield was not affected. The application of 10 mg L-1 TiO2 as nano-priming agent increased plant development and chlorophyll content under both laboratory and greenhouse conditions without translocation in the plant, which is one of the most important concerts of using nanoparticles in plant production.
Keywords: Nano-priming; priming; TiO2; tomato; seed